Inorganic nanoparticles in clinical trials and translations - Huang, Hui; Feng, Wei; Chen, Yu; Shi, Jianlin (Nano today, 2020)
[Display omitted] •The status quo of inorganic nanoparticles in clinical trials and translation is highlighted and summarized.•The progress and paradigms on inorganic nanomaterials for clinical relevance and translation are elucidated systematically.•The challenges and perspectives in clinical translation of inorganic nanoparticles are discussed in depth. The development and application of nanotechnology-related knowledge and tools in modern medicine has been showing great potentials in elevating human’s living standards and improving mankind’s healthcare conditions via the prevention, early detection, diagnosis, treatment and follow-up of various diseases. The significant progress of nanomedicine has been achieved by the exploration of nanoparticulate formulations for theranostic purposes in a living organism. Among abundant nanoparticles, inorganic nanoparticles feature distinctive physiochemical properties and biological effects, with which conventional organic counterparts are typically not endowed. In the past thirty years, to be true, very few inorganic nanomaterials have been made from bench to bedside translation. It is thus more vital than ever for the scientific community to make ever-greater efforts to realize their clinical translations. Therefore, this review highlights and discusses such a compelling topic on the clinical trials and translation of inorganic nanoparticles. We will provide an update of the current progresses in clinic-relevant applications in terms of inorganic nanoparticles being used as detecting tools, contrast agents as well as therapeutic vehicles. Especially, the crucial challenges and future prospects in translating inorganic nanoparticles into clinical practices are highlighted and outlooked. This review aims to bring the issues of clinical relevance and translatability of inorganic nanoparticles to the forefront, which is the primary impetus, and also critically important, for the development of inorganic nanoparticles-based nanobiotechnology and nanomedicine.